El no lugar de la discapacidad auditiva infantil en la cultura oyente. - Casallas Forero, Elizabeth; Arjones-Fernández, María Aurora (Multi Lingual Scientific Journals, 2022)
The research, from which this writing derives, aimed to identify the cultural realities in which a group of 24 children with hearing disabilities, togetherwith their parents, attached to an important educational institution that city of Villavicencio (Colombia). The methodology was developed from the qualitative research paradigm, using as collection strategies: the interview, social cartography, and the discussion group; After collecting the data, each of the testimonies was analyzed using the ATLAS.ti 9 software. In the results section, a description of the various forms of rejection is presented, which operate in very similar ways in three different scenarios, and are exercised from the majority culture towards the disabled population. These scenarios are: in the first instance, the family space, later the school is analyzed as a training space and, finally, a look at the neighborhood environment is given.As a general conclusion, it is evident within the presentation of results, the non-existence of a place for children with hearing disabilities, within the listening culture. The assertion is made given that it is observed in several testimonies which reveal that, in the three contexts, all kinds of adverse environments are generated. In a similar way, the existence of the phenomenon of exclusion is also evident, which is exercised from a listening majority, of the Spanish language, towards a signing cultural linguistic minority
Keywords: Niños con trastornos de audición; Educación - Fines y objetivos; Discriminación en la enseñanza; Profesores - Formación profesional; Discapacidad auditiva; Patrimonio cultural; Educacion ciudadana; Formación docente